Analysis of secondary-factor combinations of landslides using improved association rule algorithms: a case study of Kitakyushu in Japan. Issue 1 (1st January 2021) - Li, Jiaying; Wang, Wei-Dong; Han, Zheng; Chen, Guangqi
Abstract: Landslide analysis prevents landslides from threatening resident safety and property, and the predominant method is susceptibility assessment which is cumbersome and time-consuming. The association rule algorithm (ARA) is proposed to mine the correlation between the factors and landslides simply and rapidly. The original ARA cannot reflect the scope of landslides which is non-negligible for landslide analysis and is thus improved to mine the frequent secondary-factor combinations (SFCs). Firstly, eight factors are selected using the out-of-bag error and chi-squared ( χ 2 ) test. The accuracy of the factor selection is further verified employing landslide susceptibility assessment which is predicted using 30% of study grid data selected randomly as the training data. The improved ARA employs the area of historical landslides to mine the frequent SFCs, and the results are then verified by the frequency ratio and χ 2 test. It is concluded that the frequent SFCs are: (21, 41), (21, 74), (34, 41), (34, 74), (41, 74), (21, 41, 74), and (34, 41, 74), and the area with the SFCs needs special protection. The present study provides a valuable reference for the primary prevention of landslides.